Students' Perception of Formative Assessment at IIMC - Komel Zulfiqar, Shabana Ali, Amena Rahim (Journal of Islamic International Medical College, 2017)
Objective: To assess the perception of students regarding the usefulness of formative assessments. Study Design: Cross-sectional descriptive study. Place and Duration of Study: Islamic International Medical College, from January to June 2015. Materials and Methods: A structured questionnaire was distributed to 150 medical students. Response rate was 90%. There were six questions regarding the scheduling, strategy and components of formative assessment while four questions were regarding the effectiveness of formative assessment in learning. Results: It was found out that majority of the students (60%) were satisfied with placement of formative assessments in each module while 76.3% agreed that assessment were arranged regularly, though 22% disagreed with assessment plan. About 64 % students agreed that it facilitates learning process and motivates students to learn more. On the other hand only 20% students disagreed with its role in learning. Feedback and remedial were relatively weaker as only 33 % students thought that feedback was effective and timely while most of students disagreed but were satisfied with remedial offered by each discipline. Conclusion: The medical students consider formative assessment an important tool to enhance their learning process. More efforts are required to enhance the usefulness of formative assessments by improving the quality of feedback and the remedial offered for improvement.